Penerapan Contextual Teaching and Learning Berbasis Socio Scientific Issues untuk Meningkatkan Kemampuan Argumentasi Ilmiah - Amburika, Nudia; Khoiri, Ahmad; Lailiyah, Siti (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2025)
The scientific argumentation ability of students in secondary schools is still relatively low. This condition indicates the need for a learning approach that not only focuses on cognitive, but also encourages critical and argumentative thinking. This study aims to determine the effect of the Contextual Teaching and Learning (CTL) model based on Socio Scientific Issues (SSI) on improving students' scientific argumentation abilities. The study used the Quasi Experimental Design method with the form of Nonequivalent Control Group Design involving two classes X at SMA Takhassus Al Qur'an. X-I as the experimental class and X-F as the control class. The research instrument was in the form of essay questions based on the Toulmin argumentation structure indicators. The Toulmin argumentation structure consists of six main components, namely claims, data, warrants, support, qualifications, and rebuttals. Data collection was carried out using three main techniques, namely direct observation, testing through instruments (tests), and documentation. The pre-test and post-test data were analyzed using the t-test with the help of Microsoft Excel software to determine significant differences between the experimental and control groups. The results showed that the experimental class experienced a higher increase than the control class. The t-test showed a significant difference between the two classes (tcount 9.380 > ttable 1.995). The N-Gain value of 0.503 in the experimental class indicated moderate effectiveness. This finding proves that the SSI-based CTL model is effective in improving students' scientific argumentation skills as a whole.